Simulation of denitrification and ozone loss for the Arctic winter 2002/2003 - Grooß, J.-U.; Günther, G.; Müller, R.; Konopka, P.; Bausch, S.; Schlager, H.; Voigt, C.; Volk, C.M.; Toon, G. C. (Atmospheric Chemistry and Physics, 2005)
We present simulations with the Chemical Lagrangian Model of the Stratosphere (CLaMS) for the Arctic winter 2002/2003. We integrated a Lagrangian denitrification scheme into the three-dimensional version of CLaMS that calculates the growth and sedimentation of nitric acid trihydrate (NAT) particles along individual particle trajectories. From those, we derive the HNO3 downward flux resulting from different particle nucleation assumptions. The simulation results show a clear vertical redistribution of total inorganic nitrogen ( ), with a maximum vortex average permanent removal of over 5ppb in late December between 500 and 550K and a corresponding increase of of over 2ppb below about 450K. The simulated vertical redistribution of is compared with balloon observations by MkIV and in-situ observations from the high altitude aircraft Geophysica. Assuming a globally uniform NAT particle nucleation rate of 7.8x10-6cm-3h-1 in the model, the observed denitrification is well reproduced. In the investigated winter 2002/2003, the denitrification has only moderate impact (≤14%) on the simulated vortex average ozone loss of about 1.1ppm near the 460K level. At higher altitudes, above 600K potential temperature, the simulations show significant ozone depletion through -catalytic cycles due to the unusual early exposure of vortex air to sunlight.